Fibroblast growth factors signaling in bone metastasis. Issue 7 (July 2020) - Labanca, Estefania; Vazquez, Elba S; Corn, Paul G; Roberts, Justin M; Wang, Fen; Logothetis, Christopher J; Navone, Nora M
Abstract : Many solid tumors metastasize to bone, but only prostate cancer has bone as a single, dominant metastatic site. Recently, the FGF axis has been implicated in cancer progression in some tumors and mounting evidence indicate that it mediates prostate cancer bone metastases. The FGF axis has an important role in bone biology and mediates cell-to-cell communication. Therefore, we discuss here basic concepts of bone biology, FGF signaling axis, and FGF axis function in adult bone, to integrate these concepts in our current understanding of the role of FGF axis in bone metastases.